Business Performance Analysis of Purwokerto Muslim MSMe in Personality and Entrepreneur Characteristic - Muamar, Muhammad; Bagis, Fatmah (El-Barka Journal of Islamic Economics and Business, 2022)
This study is an analysis of the personality factors and characteristics of Muslim entrepreneurs on the business performance of Muslim SMEs in Purwokerto. Interestingly in this study, there are many Muslim entrepreneurs but have not run a business according to Islamic sharia. This research method uses a quantitative approach, with 55 Muslim entrepreneurs as respondents in the city of Purwokerto. The acceptance of the first and second hypotheses shows the important role of the personality and characteristics of Muslim entrepreneurs in improving the performance of Muslim SMEs.